2018
DOI: 10.5433/1679-0359.2018v39n4p1575
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of acute ruminal lactic acidosis in sheep by probiotic or monensin supplementation: clinical aspects

Abstract: The aim of this study was to evaluate the effects of two additives (probiotic and monensin) over clinical parameters of sheep submitted to acute ruminal lactic acidosis (ARLA). Eighteen sheeps were divided into three groups of six animals each as follows: probiotic group, supplemented with 4×10 9 CFU/animal/ day of Saccharomyces cerevisiae; monensin group, supplemented with 33 mg of monensin sodium per kg of diet; and control group, without any supplementation. After 30 days of diet (75% of Coast-cross hay and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The clinical observations in the goats of the two groups in this study was characteristic of RLA and the intensity of the clinical manifestations coincided with the decrease in ruminal pH, corroborating with other authors who evaluated the disease in this species under experimental conditions (CAO et al, 1987;MIRANDA NETO et al, 2005) and cases of natural occurrence (JOSHI et al, 2017). The majority of the animals in the two groups presented clinical reestablishment 48h after induction, differing from other authors who observed in sheep experimentally submitted to ruminal acidosis, early recovery in animals receiving monensin sodium in the diet, when compared to the control group, allowing the authors to infer that supplementation with ionophore contributed to faster recovery of the ruminal environment, reducing the severity of the clinical presentation (AFONSO et al, 2005;REIS et al, 2018a).…”
Section: Discussionmentioning
confidence: 73%
“…The clinical observations in the goats of the two groups in this study was characteristic of RLA and the intensity of the clinical manifestations coincided with the decrease in ruminal pH, corroborating with other authors who evaluated the disease in this species under experimental conditions (CAO et al, 1987;MIRANDA NETO et al, 2005) and cases of natural occurrence (JOSHI et al, 2017). The majority of the animals in the two groups presented clinical reestablishment 48h after induction, differing from other authors who observed in sheep experimentally submitted to ruminal acidosis, early recovery in animals receiving monensin sodium in the diet, when compared to the control group, allowing the authors to infer that supplementation with ionophore contributed to faster recovery of the ruminal environment, reducing the severity of the clinical presentation (AFONSO et al, 2005;REIS et al, 2018a).…”
Section: Discussionmentioning
confidence: 73%
“…Behaviour alterations are man-ifested by anorexia, weakness, depression, lethargy, staggering, recumbency, flank watching, and lameness (Meyer and Bryant, 2017;Pupin et al, 2017). Clinical and laboratory testing reveal pyrexia in early stage and hypothermia in later stages, tachycardia, dehydration, congestion of mucous membranes and vessels of sclera, pneumonia, metabolic acidosis, hypocalcaemia, severe toxemia, acidified urine, and ruminal atony (Snyder and Credille, 2017;Reis et al, 2018).…”
Section: Clinical Signsmentioning
confidence: 99%